Hagyományőrzés a magyar és az erdélyi óvodákban - Szonda Noémi Judit (2019)
Within the framework of the thesis, we will showcase the great days we celebrate in kindergarten education, as well as the various folklore and folk traditions in the areas of the Transilvanian. My goal was to show you the most interesting and varied traditions and habits. My research goal was to assess what parents who have a preschool child think about preschool traditions. I am also interested in how kindergarten teachers working in different educational institutions think about a folk-preservation preschool or group program. My research was carried out by means of a questionnaire survey and a written interview.